Control of brown rot (Monilinia fructicola) on organic apricots - McLaren, G.F.; Fraser, J.A. (New Zealand Plant Protection, 2000)
The effects of sulphur and copper on postharvest brown rot (Monilinia fructicola (Wint) Honey) were studied for six years in a BioGro registered apricot block at Clyde Research Centre Central Otago Four treatments of sulphur and/or copper were applied up to 9 times between flowering and harvest Brown rot levels were high in seasons with a high rainfall from November to January (harvest) Sulphur (Kumulus DF) at either 120 or 160 g ai/100 litres or at 80 g with copper (Kocide DF) at 10 g ai/100 litres reduced brown rot levels in cvs Sundrop and CluthaGold Seven organically acceptable alternatives to sulphur were also tested but none were more effective However alternatives to sulphur are needed for use close to harvest to reduce both visible residues and the possible negative effect of sulphur on return bloom